A novel enzyme-linked immunostaining technique based on silk membrane for the prenatal detection of fetomaternal haemorrhage - Li, Xinyang; Li, Miyang; Duan, Shengbao; Wang, Hongmei; Li, Yong; Liu, Tiemei (Frontiers in Bioengineering and Biotechnology, 2023)
Objective Developing a simple, rapid, reliable, sensitive, and cost-effective method for prenatal detection of fetomaternal haemorrhage by combining multi-aperture silk membrane with enzyme-linked immunosorbent assay (ELISA), which does not require any complicated instruments and can be visually colored, so as to provide a new method for clinical detection of fetomaternal haemorrhage. Methods As a carrier, a chemically treated silk membrane was used to immobilize anti-A/ anti-B antibody reagent. PBS washed slowly after vertically dropping red blood cells. After adding biotin-labeled anti-A/anti-B antibody reagent, PBS is slowly washed, enzyme-labeled avidin is added, and TMB is used for color development after washing. Results When there were both anti-A and anti-B fetal erythrocytes in pregnant women's peripheral blood, the final color was dark brown. When there are no anti-A and anti-B fetal red blood cells in pregnant women's peripheral blood, the final color development results do not change, which corresponds to the color of chemically treated silk membrane. Conclusion The new enzyme-linked immunosorbent assay (ELISA) based on a silk membrane can distinguish fetal red blood cells from maternal red blood cells prenatally and can be used for prenatal detection of fetomaternal haemorrhage.